EFEKTIVITAS MEDIA MONOPOLI BERBAHASA (MONOSA) DALAM PEMBELAJARAN TEMATIK INTEGRATIF DI SD KELAS IV - Suciati, Sri; Septiana, Ika; Untari, Mei Fita Asri (Universitas Pendidikan Indonesia, 2016)
After doing research on media Monosa second stage showed the validity of the media after the revision and implementation of media Monosa trials at several schools. Based on the validation results showed that the learning media Monosa feasible to use in the classroom IV. This learning media can also create an atmosphere of fun and do not saturate because the learning is done with playing. Based on observations made during the study, these media have an aspect of media effectiveness, efficiency media, and the media and user interest is the entry criteria. Besides media Monosa able to give meaningfulness in learning, which enhances the value of the character's ability to work together, sportsmanship, individual activeness of learners, learner independence, critical thinking, and caring.Keywords: effectiveness, media Monosa, thematic learning integrative.